2021
DOI: 10.1057/s41599-021-00969-6
|View full text |Cite
|
Sign up to set email alerts
|

Using a co-created transdisciplinary approach to explore the complexity of air pollution in informal settlements

Abstract: We present novel co-created transdisciplinary research that uses arts and humanities methods to explore air pollution in an informal settlement (Mukuru) in Nairobi, Kenya. Air pollution is a well-documented major human health issue, but despite many air pollution reduction interventions designed to improve health, these are frequently ineffective. Often this is because they fail to account for local knowledge, cultural practices and priorities of the intended recipients. Designing solutions therefore requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…However, the advantage of being flexible in the methods used means that they can respond to the iterative development of the research project, evolving to the needs of the team (Bracken et al 2015 ). In our case, the short project timeline (18 months) and primary focus of the grant being network building and experimenting with methods, left little time for integrating learning (West et al 2021 ). Ding et al ( 2020 ) highlight the need for project leaders to have explicit knowledge of integration goals, including encouraging identification of differences and discussion of these across disciplines.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, the advantage of being flexible in the methods used means that they can respond to the iterative development of the research project, evolving to the needs of the team (Bracken et al 2015 ). In our case, the short project timeline (18 months) and primary focus of the grant being network building and experimenting with methods, left little time for integrating learning (West et al 2021 ). Ding et al ( 2020 ) highlight the need for project leaders to have explicit knowledge of integration goals, including encouraging identification of differences and discussion of these across disciplines.…”
Section: Resultsmentioning
confidence: 95%
“…The project generated a range of products for both community and academic audiences, as shown in Table 3 . For more details, see West et al ( 2021 ). Some products were temporary (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulties of behaviour change in the 'real-world' are imitated with the other actors opposing the proposed changes of the spect-actor. West et al [100], developed forum theatre storylines from community members own accounts of how air quality had affected them and presented the play at various community hubs around Mukuru (an informal settlement in Kenya), allowing community members to contribute to the scene and offer their suggestions for resolving the various issues. It has been suggested that the personal relevance of forum theatre is a key motivator for individual behaviour change [101].…”
Section: More Participatory Engagementmentioning
confidence: 99%
“…Instead of developing interventions 'for', this approach develops interventions 'with' relevant stakeholders that fit the needs and priorities of those they impact [104]. For example, West et al [100], using creative methods in a co-production approach, found that this enabled the production of several solutions to air pollution which were designed around and suitable for the local context informed by communities' priorities and contributing towards "improved outcomes and achievable solutions" [105]. Where there is a need to induce behaviour change, co-production is believed to be particularly valuable [106], yet the value of such research is only now being realised for the 'wicked' issue of air pollution.…”
Section: More Participatory Engagementmentioning
confidence: 99%